2020
DOI: 10.1055/s-0040-1701922
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Polymerization Technique and Glass-Fiber Reinforcement on the Flexural Properties of Denture Base Resin Material

Abstract: Objective Different polymerization and reinforcement techniques have been tested to enhance the mechanical characteristics of denture base acrylic resins. The goal of the present study was to evaluate the influence of autoclave polymerization techniques with glass fiber reinforcement on the flexural strength and elastic modulus of polymethyl methacrylate denture base resins. Materials and Methods Ninety specimens were fabricated from heat-polymerized acrylic resin and randomly distributed depending on the poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 31 publications
(46 reference statements)
4
18
0
Order By: Relevance
“…Therefore, good mechanical properties are required for the functional performance of denture base materials (biofunctionality). Considering the significance of the mechanical properties, several modifications have been reported for various mechanical properties of PMMA, including its flexural strength [ 14 , 30 , 33 , 68 , 134 , 135 , 136 ], impact strength [ 14 , 137 , 138 , 139 , 140 ], fracture toughness [ 141 , 142 , 143 ], and surface hardness [ 67 , 98 , 141 , 144 , 145 ]. The flexural strength (also known as the modulus of rupture or transverse strength) is assessed using a 3-point bending test according to the guidelines of ISO 20795-1 [ 81 ].…”
Section: Properties Of Pmmamentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, good mechanical properties are required for the functional performance of denture base materials (biofunctionality). Considering the significance of the mechanical properties, several modifications have been reported for various mechanical properties of PMMA, including its flexural strength [ 14 , 30 , 33 , 68 , 134 , 135 , 136 ], impact strength [ 14 , 137 , 138 , 139 , 140 ], fracture toughness [ 141 , 142 , 143 ], and surface hardness [ 67 , 98 , 141 , 144 , 145 ]. The flexural strength (also known as the modulus of rupture or transverse strength) is assessed using a 3-point bending test according to the guidelines of ISO 20795-1 [ 81 ].…”
Section: Properties Of Pmmamentioning
confidence: 99%
“…Ideally, the denture base should have a high flexural strength to bear the complex forces of mastication without permanent deformation or fracture [ 9 ]. A number of studies have investigated [ 14 , 30 , 33 , 68 , 134 , 135 , 136 ] flexural strength using various methods and types of PMMA. Barbrosa et al [ 146 ] reported good flexural strength for heat-cured, cold-cured, and microwave-cured PMMA (92.84 ± 4.73, 84.40 ± 1.68, and 109.63 ± 5.31 MPa, respectively).…”
Section: Properties Of Pmmamentioning
confidence: 99%
See 2 more Smart Citations
“…Heat-polymerized acrylic resin is commonly used to fabricate definitive complete and partial removable dental prostheses ( Polychronakis et al, n.d. ). It has the features of a natural intra-oral appearance; biocompatibility; simple processing, finishing, and polishing techniques; and cost efficiency ( Al-Thobity, 2020 , Gad et al, 2019b ). However, it has low flexural strength and toughness.…”
Section: Introductionmentioning
confidence: 99%